Chemostratigraphy of the Ordovician Sarah Formation, North West Saudi Arabia: An integrated approach to reservoir correlation. (November 2016) - Craigie, Neil W.; Rees, Andrew; MacPherson, Keith; Berman, Seth
Abstract: Late Ordovician pre-glacial and syn-glacial deposits form economically important hydrocarbon reservoirs throughout North Africa and the Arabian Peninsula. Internal subdivision of the unit is difficult due to the short time span of deposition resulting in coarse biostratigraphic control. The arenaceous character of the sediments has also contributed to poor biostratigraphic recovery. The present study focuses on the chemostratigraphic correlation of this interval encountered in ten wells across a complex, multi-phased pro-glacial outwash fan dominated by hyperpycnal (jet-efflux) turbidites fed by glacial outburst floods. The high resolution reservoir layering scheme presented here utilizes detailed sedimentological core descriptions, borehole image-derived palaeoflow indicators, 3D seismic attributes and chemostratigraphy. The Inductively Coupled Plasma – Optical Emission Spectrometry (ICP-OES) and Inductively Coupled Plasma – Mass Spectrometry (ICP-MS) techniques were used to acquire data for 50 elements, with the chemostratigraphic scheme based on changes in the following 'key' element ratios: Zr/Y, Zr/Lu, Th/Nb, Th/P, Ta/P, Cr/P, P/Lu, Th/Ti, Cr/Yb and Th/Ta. G may give the impression that there are two principal aims are defined by distinct values of key element ratios, with variations in these mainly reflecting changes in source/provenance. In order to avoid complications relating to changes in grain size/lithology, separate schemes were proposed for sandstone and mudrock lithologies, with the former comprising a hierarchical order of two zones, three subzones and seven divisions. Owing to the lower number of analyzed mudrocks, the scheme produced for this dataset is less detailed but, nevertheless, consists of three principal zones and five subzones. At the formation level, chemical stratigraphy allowed for consistent identification and correlation of the pre-glacial Qasim, syn-glacial Sarah and post-glacial Qalibah formations. The earliest post-glacial unit referred to as the Uqlah Formation has an inherited signature from the syn-glacial chemozone (i.e. uppermost Sarah Formation) below, and represents initial reworking of the post-glacial landscape following isostatic rebound. Evidence for glacial isostasy is recorded in a regional deformed zone at the top of the Sarah Formation and immediately beneath an isostatic rebound unconformity at the base of the Uqlah Formation. Chemical zonation of this unit clearly illustrates significant local truncation in wells located close to NW-SE trending lineaments. It is proposed that chemozones are missing across reactivated fault block highs as a result of increased erosion on the shallow marine post glacial shelf. High resolution reservoir layering of the hydrocarbon-bearing syn-glacial Sarah Formation highlights a complex depositional system characterized by an initial phase of deeply entrenched pro-glacial turbidite channels and younger sheet-like depositional lobes. Cores and image logs from both elements of the outwash fan system record extensive climbing dune cross-bedding, an unusual sedimentary structure described from many Upper Ordovician glacial successions in North Africa, and considered indicative of quasi-steady sediment-charged flows initiated by glacial outburst floods. There is no shared chemical link between the lowest channels and overlying lobes, suggesting a large fan system may be found downdip of this deeper channel system. Integration of the zonation scheme with 3D seismic attribute analysis clearly illustrates a second and even third phase of small channels cross cutting the lower larger vintage that fed the sheet-like younger lobe system. This is substantiated by a shared chemical signature and provenance between these small channels and their attached lobes. Highlights: Produced a chemostratigraphic scheme comprising a hierarchical order of zones, subzones, divisions and subdivisions. Zonation is largely based on based on variations in elemental ratios reflecting changes in source/provenance. Sarah Formation comprises turbidite channels which are succeeded by fan deposits. Chemostratigraphy resulted in a high level of resolution and the correlation of individual beds.